The Relationship between the Kind of Delivery and 5 Indexes of Mother and Baby\'s Health Before and After Implementing Health Reform Plan in Selected Hospitals of East Azerbaijan (Iran) - Hossein Jabari; Bayaneh Seyedamini; Elahe Navvabi; Salah Asadi (Shahid Sadoughi University of Medical Sciences, 2019)
Background: To improve the individuals' health, reforms should be made in the health systems. As a result, assessing the impacts of reforms is a way to evaluate the effectiveness of the health system. The aim of this study was to study the relationship between the kind of delivery and the five indexes of mother and baby's health before and after implementing the health reform plan in selected hospitals of East Azerbaijan, Iran. Methods: This descriptive-analytical study was conducted in 2018. The study was conducted among eight educational, medical, and private hospitals. Before and after the program, 800 files were selected using simple random sampling method. The researcher made a check list with confirmed validity to extract the data. The data were analyzed using descriptive statistics and T-tests by SPSS-22. Results: The average age of mothers in the two intervals was 27 years. Most participants did not deliver before and their education was diploma or lower. The rate of natural delivery from 34.5% (before the plan) reached 44.2% (after the plan)(p<0.05). The rate of mothers and babies' mortality reduced from 0.3 and 0.8 to 0 and 0.5, respectively. Mothers and babies' mortality and stillbirth had no significant difference based on the kind of delivery (p>0.05). Conclusion: Findings indicated significant increase of natural delivery after the reform plan in health system. Moreover, the rate of mothers and babies' mortality decreased. These results can guide the policymakers for deciding about the course of plan and its review.